DIRECTING A DRAMA-COMEDY FILM ENTITLED “HANI” - Mahammad Saleh; Cito Yasuki Rahmad (Institut Seni Indonesia Surakarta, 2021)
Early marriage remains a social problem, especially among less-educated urban people, including in Tamanan District, Bondowoso Regency, East Java Province. The community has a distinctive and unique Pandalungan language that offers an interesting idea source for filmmaking. Thus, this creation seeks to illustrate how “Hani”, a drama-comedy film, was directed with a local-culture approach. The production of “Hani” referred to the existing Standard Operating Procedures (SOP) in the audiovisual profession and combined the visual comedy and slapstick approaches. The direction of “Hani” indicates that using local culture (Pandalungan language) in each storyline and local actor character can create an entertaining and educating comedy film. Further, the film produced is an audiovisual work that is easily understandable by the local community.